GE_GERICHTE P/26729/2023 vom 19. Juli 2024 - GE Cour de justice (2024)
DÉCISION D'IRRECEVABILITÉ;SOUPÇON;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);LÉSION CORPORELLE SIMPLE;VIOLATION DE DOMICILE | CPP.310; CP.123; CP.144; CP.186